Sealing and adaptation of different biomaterials used in the protection of the pulpal dentin complex - Sakalian, María Candela; Rozas, Carlos Alfredo; Uribe Echevarría, Leonardo; Visvisían, Carmen (Sociedad Uruguaya de Investigación Odontológica, 2022)
Fil: Sakalian, María Candela . Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Endodoncia A; Argentina.